2000
DOI: 10.1164/ajrccm.161.5.9904121
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Polysomnographic Features of Obstructive Sleep Apnea

Abstract: We examined the influence of gender on the polysomnographic features of obstructive sleep apnea (OSA) in a retrospective study of 830 patients with OSA diagnosed by overnight polysomnography (PSG). The severity of OSA was determined from the apnea- hypopnea index (AHI) for total sleep time (AHI(TST)), and was classified as mild (5 to 25 events/h), moderate (26 to 50 events/h), and severe (> 50/events/h). Differences in OSA during different stages of sleep were assessed by comparing the AHI during non-rapid eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
219
10
22

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(286 citation statements)
references
References 22 publications
35
219
10
22
Order By: Relevance
“…In the case of AHT, despite the existence of epidemiological studies that point to SAHS as a causal factor of diurnal AHT [4,5], study of the adverse effect of blood pressure in these patients may require analysis of its nocturnal behaviour [3,30]. Finally, although particular characteristics of SAHS have been described in females [31] and a preliminary study pointed to a possible increase in mortality [32], no differences were found according to sex.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of AHT, despite the existence of epidemiological studies that point to SAHS as a causal factor of diurnal AHT [4,5], study of the adverse effect of blood pressure in these patients may require analysis of its nocturnal behaviour [3,30]. Finally, although particular characteristics of SAHS have been described in females [31] and a preliminary study pointed to a possible increase in mortality [32], no differences were found according to sex.…”
Section: Discussionmentioning
confidence: 99%
“…Its effect is suggested by studies demonstrating improvements in critical pressure and sleep apnea after weight loss (25,116). Central adiposity may lead to disturbances in neuromuscular control because men have a greater severity of sleep apnea in clinical and community-based cohorts than do women (1), and even lean men demonstrate subtle defects in upper airway neuromuscular responses to mechanical loads compared with lean women (87,(117)(118)(119)(120). These findings are consistent with the notion that central obesity is associated with a marked blunting of upper airway neuromuscular responses (Figure 1), although the mechanisms linking regional adiposity and neural responses have not been delineated.…”
Section: Neuromuscular Effects Of Obesitymentioning
confidence: 99%
“…In studies that used diagnostic criteria similar to ours, AHI have ranged between 10% and 13% (16,17 Because of differences in the definition criteria, in cases with REM-related OSAS, clinical characteristics also demonstrate differences. In many studies, a higher incidence of REM-related OSAS has been reported in women (3,6,12,13,19,20). Higher AHI REM relative to AHI NREM in women suggest the protection of women from respiratory events in NREM sleep.…”
Section: Discussionmentioning
confidence: 95%